Nigeria : Expanding Access to Rural Infrastructure Issues and Options for Rural Electrification, Water Supply and Telecommunications - World Bank (Washington, DC, 2014)
Over two thirds of Nigeria's population resides in rural areas. Increasingly, poverty in the country is wearing a rural face. From 28.3 percent in 1980, poverty among the rural population grew to 51.4 percent in 1985, has since risen to 69.8 percent in 1996. Poverty tends to affect men and women differently. Women are generally less educated, more vulnerable, deprived and powerless than their male counterparts. 1.2 Poor people experience insecurity and vulnerability (drought, desertification, flooding, deforestation, diseases, volatile commodity markets etc.); lack of empowerment to influence public policies according to their priorities; and lack of opportunities for income generation and benefits from markets. Access to education, safe water supply, sanitation, health, modern energy, telecommunications and roads are important in reducing vulnerability and increasing prosperity.